Gas jet targets for direct reaction studies - Chipps, K. A. (Frontiers in Physics, 2025)
The study of direct reactions is of broad interest in nuclear physics, providing constraint to models of nuclear structure evolution and data to better understand the creation of the elements. In many cases, however, the data of interest are hindered by backgrounds and poor resolution from contaminants in either the beam, the target, or both. The use of a gas jet can overcome some of these issues through clever engineering, providing a reaction target that is chemically pure and thin enough to significantly reduce the impact on experimental resolution. This Perspective will discuss the effort to design, construct, and operate gas jet targets for direct reaction studies in the rare isotope era.